The role of Disorder Eating in Athlete Performance in China - Du Yufeng; Quan Zhao; Lu Xiaochun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The objective of this study is to examine the role of disorder eating in athlete performance. To examine the role of disorder eating in athlete performance, the role of disorder eating, energy deficiency, negative eating behavior and demotivation is also considered. Therefore, the relationship between disorder eating, energy deficiency, negative eating behavior, demotivation and athlete performance has been examined through the course of the present study. To this end, a total of nine hypotheses are proposed in this study including six direct hypotheses and three indirect hypotheses. Data is collected from a population of athletes in China and a questionnaire is used the main instrument for data collection wherein a Likert scale is used on account of its suitability for collecting the opinion and views of individuals. After analyzing the data using a statistical tool, it is observed that disorder eating has an important role in athlete performance. It is found that; disorder eating has a positive effect on energy deficiency. It also has positive effect on negative eating behavior. Disorder eating is found to have a positive effect on demotivation. Furthermore, energy deficiency has negative effects on athlete performance. Negative eating behavior has a negative effect on athlete performance. Finally, demotivation also has negative effect on athlete performance.